(untitled) (Jurnal Ilmu Pendidikan dan Sains: Visioedusains, 2025)
This study aims to analyze the influence of the Project Based Learning (PjBL) learning model on student creativity and environmental literacy on environmental pollution materials at MTs NW Pengadang, Central Lombok Regency. This study uses a quasi-experimental method with a non-equivalent control group design. The sampling technique was carried out through simple random sampling, with a total sample of 42 students divided into experimental and control groups. The instruments used in data collection include observation sheets to measure student creativity and questionnaires to assess the level of environmental literacy. The data obtained was analyzed using the MANOVA (Multivariate Analysis of Variance) test, to determine the influence of the learning model on both dependent variables simultaneously. The results of the analysis showed that the PjBL learning model had a significant influence on increasing student creativity, which was shown by a significance value of 0.00 (p < 0.05). In addition, the application of the PjBL model also had a significant impact on improving students' environmental literacy, with the same significance value, namely 0.00 (p < 0.05). Thus, it can be concluded that the implementation of the project-based learning model is able to improve students' creative thinking skills as well as students' awareness of environmental issues. These findings recommend the application of PjBL as an effective learning approach to integrate students' cognitive and affective aspects, especially in science learning that is contextual and relevant to daily life.